Design and synthesis of a series of bioavailable fatty acid synthase (FASN) KR domain inhibitors for cancer therapy. Issue 12 (1st July 2018) - Lu, Tianbao; Schubert, Carsten; Cummings, Maxwell D.; Bignan, Gilles; Connolly, Peter J.; Smans, Karine; Ludovici, Donald; Parker, Michael H.; Meyer, Christophe; Rocaboy, Christian; Alexander, Richard; Grasberger, Bruce; et al.
Graphical abstract: Highlights: A new series of imidazolinone fatty acid synthase inhibitors. Crystal structure shows binding to the fatty acid synthase ketoreductase domain. Strong antiproliferative activity in several cancer cell lines. Favorable ADME properties and significant oral exposure in mice. Abstract: We designed and synthesized a new series of fatty acid synthase (FASN) inhibitors with potential utility for the treatment of cancer. Extensive SAR studies led to highly active FASN inhibitors with good cellular activity and oral bioavailability, exemplified by compound 34 . Compound 34 is a potent inhibitor of human FASN (IC50  = 28 nM) that effectively inhibits proliferation of A2780 ovarian cells (IC50  = 13 nM) in lipid-reduced serum (LRS). This cellular activity can be rescued by addition of palmitate, consistent with an on-target effect. Compound 34 is also active in many other cell types, including PC3M (IC50  = 25 nM) and LnCaP-Vancouver prostate cells (IC50  = 66 nM), and is highly bioavailable (F 61%) with good exposure after oral administration. In a pharmacodynamics study in H460 lung xenograft-bearing mice, oral treatment with compound 34 results in elevated tumor levels of malonyl-CoA and decreased tumor levels of palmitate, fully consistent with the desired target engagement.